Climate modes synergistically influence marine heatwaves in the North Sea - Yuxin Lin; Zhiqiang Liu; Feng Zhou; Qicheng Meng; Wenyan Zhang (Ocean Science, 2026)
Global shelf seas have experienced unprecedented marine heatwaves (MHWs) in recent decades. Although MHWs have been extensively studied at the global scale, their regional variability and underlying mechanisms remain poorly understood, particularly in shelf seas influenced by multiple climate modes. Here, we examine MHW variability in the Northeastern Atlantic shelf using a correlation-based k-means clustering approach. Two distinct subregions with contrasting seasonal patterns are identified. In winter, the southern North Sea experiences increased MHW frequency, intensity, and duration. This enhancement is linked to a positive East Atlantic Pattern, which intensifies westerly winds and enhances warm Atlantic inflow through both atmospheric and oceanic pathways. In contrast, the northern North Sea shows enhanced MHW frequency and duration in summer, while MHW intensity weakens. This summer response is modulated by Atlantic Multidecadal Variability, with its positive phase strengthening Pacific–Atlantic connections via Rossby wave propagation, altering cloud cover and surface radiative forcing. A shallow mixed layer, enhanced stratification, and circulation-induced upwelling favor frequent and persistent but less intense summer MHWs. This north–south contrast demonstrates that different combinations of atmospheric and oceanic processes shape MHW variability across the shelf, providing a diagnostic and mechanistic framework for understanding regional MHW variability and its potential predictability.

The North Atlantic mean state in mesoscale eddy-resolving coupled models: a multimodel study - Amanda Frigola; Eneko Martin-Martinez; Eduardo Moreno-Chamarro; Margarida Samsó; Saskia Loosvelt-Tomas; Pierre-Antoine Bretonnière; Daria Kuznetsova; Xia Lin; Pablo Ortega (Ocean Science, 2025)
Ocean mesoscale structures, which are parameterized in models with standard resolutions on the order of 1° or coarser, have an impact at larger scales, affecting the ocean mean state and circulation. Here we study the effects of increasing model ocean resolution to mesoscale eddy-resolving scales on the representation of the North Atlantic mean state, by comparing an ensemble of four HighResMIP coupled historical simulations with nominal ocean resolutions of at least 1/10° – corresponding to the models CESM1-CAM5-SE-HR, EC-Earth3P-VHR, HadGEM3-GC31-HH, and MPI-ESM1-2-ER – to a baseline of 39 Coupled Model Intercomparison Project phase 6 (CMIP6) simulations at coarser resolution. We find an improved representation of the Gulf Stream (GS) structure and position in the mesoscale-resolving ensemble, which leads to significantly reduced surface temperature and salinity biases north of Cape Hatteras (NCH). While higher resolution lessens the mean cold–fresh surface biases in the Central North Atlantic (CNA), the improvement is not statistically significant, as some mesoscale-resolving models still present an overly weak North Atlantic Current (NAC). Important differences also occur in the Labrador (LS) and western Irminger Seas (IS). Although the mesoscale-resolving ensemble exhibits larger warm and salty local biases at the surface compared to the low-resolution one, its full-depth profile reveals significantly weaker vertical stratification in the area, closer to observations. This reduced stratification in the high-resolution ensemble is consistent with the presence of stronger (although not significantly stronger) deep water convection in the region. While in the LS the wide range of MLD observational estimates makes model assessment challenging, in the Nordic Seas and along the East Greenland Current, convection in the high-resolution model ensemble is in better agreement with observational records, compared to the low-resolution ensemble. Another clear improvement in the mesoscale-resolving ensemble is found for the representation of the Atlantic overturning in depth-space, which is significantly closer to RAPID observations at 26.5° N than in the low-resolution counterpart; however, it still remains too shallow compared to observations and reanalyses. The subpolar gyre (SPG), as characterized by the barotropic streamfunction, is not significantly stronger in the higher resolution ensemble, although it presents a narrower and locally stronger boundary current.

Interannual variability of summertime cross-isobath exchanges in the northern South China Sea: ENSO and riverine influences - Yunping Song; Yuxin Lin; Peng Zhan; Zhiqiang Liu; Zhongya Cai (Ocean Science, 2025)
This study, combining long-term observations and high-resolution simulations, investigates the interannual variability of summer shelf circulation in the Northern South China Sea (NSCS) from 2000 to 2022. We elucidate the responses of NSCS shelf circulation to ENSO and Pearl River Estuary (PRE) freshwater runoff, revealing distinct spatial and mechanistic signatures. During El Niño years, a pronounced sea level anomaly dipole forms between the central and southern South China Sea, intensifying northward geostrophic currents in the southern basin and modulating Kuroshio intrusions. Simultaneously, an amplified PRE plume extends eastward to the 100 m isobath, markedly reducing nearshore salinity. Analysis of depth-integrated vorticity equations indicates that the pressure gradient force – driven by the joint effect of baroclinicity and bottom relief (JEBAR) and bottom pressure gradients – governs NSCS circulation variability. In coastal regions, cross-isobath velocity anomalies are primarily controlled by bottom stress curl and nonlinear vorticity advection, whereas JEBAR dominates offshore dynamics beyond the 100 m isobath. During El Niño summers, bottom density anomalies generate positive cross-isobath velocity anomalies through JEBAR, partially offset by negative anomalies from altered vertical stratification, sustaining a meandering shelf current. These results highlight the interplay of regional and remote forcings, advancing understanding of NSCS hydrographic dynamics.

Evolutions of the seasonal anticyclonic circulation around the Qingdao cold water mass in the China marginal sea and its mechanism - Lin Lin; Hans von Storch; Yang Ding (Ocean Science, 2025)
The circulation structure surrounding the Qingdao cold water mass in 2019 was investigated using three-dimensional ensembles of numerical simulations. This study reveals that a cold pool appears in early spring and reaches its peak in late May, and this pool is accompanied by local seasonal anticyclonic circulation. Momentum diagnostics reveal that vertical friction cannot be ignored because of the shallow topography and surface wind stress; as a result, the geostrophic balance is inapplicable in the Qingdao cold water mass region. Seasonal circulation mostly results from the balance of the pressure gradient, Coriolis, and vertical friction forces. The no-tide and no-wind numerical simulation results suggest that when the tidal forcing is turned off, unrealistically strong currents appear and are caused by the decrease in vertical friction in the no-tide simulation. Moreover, the direction of the eastern side of the anticyclonic circulation is reversed. Furthermore, the seasonal southwesterly monsoon contributes to the magnitude of the anticyclonic circulation, especially in the western portion of the anticyclonic circulation, by piling up the surface water eastward and further changing barotropic pressure gradient force. Additionally, upwelling occurs vertically around the Qingdao cold water mass and is influenced by tidal and wind forcings. The wind forcing affects upwelling (especially in the western part), which can be explained by Ekman pumping; the tides contribute to upwelling in the eastern part by reshaping the thermocline and further changing the barotropic and baroclinic pressure gradient force. Ensemble simulations are used, and a t test reveals that 51 % (90 %) of points, difference between the control run and the ensemble experiments without tidal forcing (and without wind forcing) is statistically significant.

The different dynamic influences of Typhoon Kalmaegi on two pre-existing anticyclonic ocean eddies - Yihao He; Xiayan Lin; Guoqing Han; Yu Liu; Han Zhang (Ocean Science, 2024)
Using multi-source observational data and GLORYS12V1 reanalysis data, we conduct a comparative analysis of different responses of two warm eddies, AE1 and AE2 in the northern South China Sea, to Typhoon Kalmaegi during September 2014. The findings of our research are as follows: (1) for horizontal distribution, the area and the sea surface temperature (SST) of AE1 and AE2 decrease by about 31 % (36 %) and 0.4 °C (0.6 °C). The amplitude, Rossby number (Ro = relative vorticity / Coriolis parameter) and eddy kinetic energy (EKE) of AE1 increase by 1.3 cm (5.7 %), 1.4×10-2 (20.6 %) and 107.2 cm2 s−2 (49.2 %) after the typhoon, respectively, while AE2 weakens and the amplitude, Rossby number and EKE decrease by 3.1 cm (14.6 %), 1.6×10-2 (26.2 %) and 38.5 cm2 s−2 (20.2 %), respectively. (2) In the vertical direction, AE1 demonstrates enhanced convergence, leading to an increase in temperature and a decrease in salinity above 150 m. The response below the mixed-layer depth (MLD) is particularly prominent (1.3 °C). In contrast, AE2 experiences cooling and a decrease in salinity above the MLD. Below the MLD, it exhibits a subsurface temperature drop and salinity increase due to the upwelling of cold water induced by the suction effect of the typhoon. (3) The disparity in the responses of the two warm eddies can be attributed to their different positions relative to Typhoon Kalmaegi. Under the influence of negative wind stress curl outside the maximum wind radius (Rmax) of the typhoon, triggering negative Ekman pumping velocity (EPV) and quasi-geostrophic adjustment of the eddy, the warm eddy AE1, with its center to the left of the typhoon's path, further enhances the converging sinking of the upper warm water, resulting in its intensification. On the other hand, the warm eddy AE2, situated closer to the center of the typhoon, weakens due to the cold suction caused by the strong positive wind stress curl within the typhoon's Rmax. The same polarity eddies may have different response to typhoons. The distance between eddies and typhoons, eddy intensity, and the background field need to be considered.

Salt intrusion dynamics in a well-mixed sub-estuary connected to a partially to well-mixed main estuary - Zhongyuan Lin; Guang Zhang; Huazhi Zou; Wenping Gong (Ocean Science, 2024)
Salt intrusion in estuaries has been exacerbated by climate change and human activities. Previous studies have primarily focused on salt intrusion in the mainstem of estuaries, whereas those in sub-estuaries (those that branch off their main estuaries) have received less attention. During an extended La Niña event from 2021 to 2022, a sub-estuary (the East River estuary) alongside the Pearl River estuary, China, experienced severe salt intrusions, posing a threat to the freshwater supply in the surrounding area. Observations revealed that maximum salinities in the main estuary typically preceded spring tides, exhibiting significant asymmetry in salinity rise and fall over a fortnightly timescale. In contrast, in the upstream region of the sub-estuary, the variation in salinity was in phase with that of the tidal range, and the rise and fall of the salinity were more symmetrical. Inspired by these observations, we employed idealized numerical models and analytical solutions to investigate the underlying physics behind these behaviors. It was discovered that under normal dry conditions (with a river discharge of 1500 m3 s−1 at the head of the main estuary), the river–tide interaction and change in horizontal dispersion accounted for the in-phase relationship between the salinity and tidal range in the upstream region of the sub-estuary. Under extremely dry conditions (i.e., a river discharge of 500 m3 s−1 at the head of the main estuary), salinity variations were in phase with those of the tidal range in the middle as well as the upstream region of the sub-estuary. The variation in salinity in the main estuary along with those in salt dispersion and freshwater influx inside the sub-estuary collectively influenced salinity variation in the well-mixed sub-estuary. These findings have important implications for water resource management and salt intrusion prevention in the catchment area.

Delayed-mode reprocessing of in situ sea level data for the Copernicus Marine Service - Jue Lin-Ye; Begoña Pérez Gómez; Alejandro Gallardo; Fernando Manzano; Marta de Alfonso; Elizabeth Bradshaw; Angela Hibbert (Ocean Science, 2023)
The number of tide gauges providing coastal sea level data has significantly increased in recent decades. They help in the issue of coastal hazard warnings, in the forecasting (indirectly through models) of storm surges and tsunamis, and in operational oceanography applications. These data are automatically quality controlled in near-real time in the Copernicus Marine Service. A new initiative seeks to provide delayed-mode reprocessed data for the Copernicus Marine Service by developing a new product and upgrading the software used in its automated quality control. Several new modules, such as buddy checking or the detection of attenuated data, are implemented. The new product was launched in November of 2022. The entire reprocessing is discussed in detail. An example of the information that can be extracted from the delayed-mode reprocessed product is also given.

Data-assimilation-based parameter estimation of bathymetry and bottom friction coefficient to improve coastal accuracy in a global tide model - Xiaohui Wang; Martin Verlaan; Jelmer Veenstra; Hai Xiang Lin (Ocean Science, 2022)
Global tide and surge models play a major role in forecasting coastal flooding due to extreme events or climate change. The model performance is strongly affected by parameters such as bathymetry and bottom friction. In this study, we propose a method that estimates bathymetry globally and the bottom friction coefficient in shallow waters for a global tide and surge model (GTSMv4.1). However, the estimation effect is limited by the scarcity of available tide gauges. We propose complementing sparse tide gauges with tide time series generated using FES2014. The FES2014 dataset outperforms the GTSM in most areas and is used as observations for the deep ocean and some coastal areas, such as Hudson Bay and Labrador, where tide gauges are scarce but energy dissipation is large. The experiment is performed with a computation- and memory-efficient iterative parameter estimation scheme (time–POD-based coarse incremental parameter estimation; POD: proper orthogonal decomposition) applied to the Global Tide and Surge Model (GTSMv4.1). Estimation results show that model performance is significantly improved for the deep ocean and shallow waters, especially in the European shelf, directly using the CMEMS tide gauge data in the estimation. The GTSM is also validated by comparing to tide gauges from UHSLC, CMEMS, and some Arctic stations in the year 2014.

Anomalous distribution of distinctive water masses over the Carlsberg Ridge in May 2012 - Hailun He; Yuan Wang; Xiqiu Han; Yanzhou Wei; Pengfei Lin; Zhongyan Qiu; Yejian Wang (Ocean Science, 2020)
In May 2012, we conducted a hydrographic survey over the Carlsberg Ridge in the northwest Indian Ocean. In this paper, we use these station data, in combination with some free-floating Argo profiles, to obtain the sectional temperature and salinity fields, and subsequently, the hydrographic characteristics are comprehensively analyzed. Through the basic T–S diagram, three salty water masses, Arabian Sea High-Salinity Water, Persian Gulf Water, and Red Sea Water, are identified. The sectional data show a clear ventilation structure associated with Arabian Sea High-Salinity Water. The 35.8 psu salty water sinks at 6.9∘ N and extends southward to 4.4∘ N at depths around the thermocline, where the thermocline depth is in the range of 100 to 150 m. This salty thermocline extends much further south than climatology indicates. Furthermore, the temperature and salinity data are used to compute the absolute geostrophic current over the specific section, and the results show mesoscale eddy vertical structure different from some widely used oceanic reanalysis data. We also find a west-propagating planetary wave at 6∘ N, and the related features are described in terms of phase speed and horizontal and vertical structures.

Tidal variability in the Hong Kong region - Adam T. Devlin; Jiayi Pan; Hui Lin (Ocean Science, 2019)
Mean sea level (MSL) is rising worldwide, and correlated changes in ocean tides are also occurring. This combination may influence future extreme sea levels, possibly increasing coastal inundation and nuisance flooding events in sensitive regions. Analyses of a set of tide gauges in Hong Kong reveal complex tidal behavior. Most prominent in the results are strong correlations of MSL variability to tidal variability over the 31-year period of 1986–2016; these tidal anomaly correlations (TACs) express the sensitivity of tidal amplitudes and phases (M2, S2, K1, O1) to MSL fluctuations and are widely observed across the Hong Kong region. At a few important harbor locations, time series of approximations of the parameter δ-HAT, computed from combinations of the major tidal constituents, are found to be highly sensitive to MSL variability, which may further increase local flood levels under future MSL rise. Other open-water locations in Hong Kong only show TACs for some individual tidal constituents but not for combined tidal amplitudes, suggesting that the dynamics in enclosed harbor areas may be partially frequency dependent and related to resonance or frictional changes. We also observe positive correlations of the fluctuations of diurnal (D1) tides to semidiurnal (D2) tides at most locations in the region, which may lead to further amplified tidal ranges under MSL. It is demonstrated here that tidal changes in the Hong Kong coastal waters may be important in combination with MSL rise in impacting future total water levels.

The land–sea coastal border: a quantitative definition by considering the wind and wave conditions in a wave-dominated, micro-tidal environment - Agustín Sánchez-Arcilla; Jue Lin-Ye; Manuel García-León; Vicente Gràcia; Elena Pallarès (Ocean Science, 2019)
A quantitative definition for the land–sea (coastal) transitional area is proposed here for wave-driven areas, based on the variability and isotropy of met-ocean processes. Wind velocity and significant wave height fields are examined for geostatistical anisotropy along four cross-shore transects on the Catalan coast (north-western Mediterranean), illustrating a case of significant changes along the shelf. The variation in the geostatistical anisotropy as a function of distance from the coast and water depth has been analysed through heat maps and scatter plots. The results show how the anisotropy of wind velocity and significant wave height decrease towards the offshore region, suggesting an objective definition for the coastal fringe width. The more viable estimator turns out to be the distance at which the significant wave height anisotropy is equal to the 90th percentile of variance in the anisotropies within a 100 km distance from the coast. Such a definition, when applied to the Spanish Mediterranean coast, determines a fringe width of 2–4 km. Regarding the probabilistic characterization, the inverse of wind velocity anisotropy can be fitted to a log-normal distribution function, while the significant wave height anisotropy can be fitted to a log-logistic distribution function. The joint probability structure of the two anisotropies can be best described by a Gaussian copula, where the dependence parameter denotes a mild to moderate dependence between both anisotropies, reflecting a certain decoupling between wind velocity and significant wave height near the coast. This wind–wave dependence remains stronger in the central bay-like part of the study area, where the wave field is being more actively generated by the overlaying wind. Such a pattern controls the spatial variation in the coastal fringe width.

Effect of winds and waves on salt intrusion in the Pearl River estuary - Wenping Gong; Zhongyuan Lin; Yunzhen Chen; Zhaoyun Chen; Heng Zhang (Ocean Science, 2018)
Salt intrusion in the Pearl River estuary (PRE) is a dynamic process that is influenced by a range of factors and to date, few studies have examined the effects of winds and waves on salt intrusion in the PRE. We investigate these effects using the Coupled Ocean-Atmosphere-Wave-Sediment Transport (COAWST) modeling system applied to the PRE. After careful validation, the model is used for a series of diagnostic simulations. It is revealed that the local wind considerably strengthens the salt intrusion by lowering the water level in the eastern part of the estuary and increasing the bottom landward flow. The remote wind increases the water mixing on the continental shelf, elevates the water level on the shelf and in the PRE and pumps saltier shelf water into the estuary by Ekman transport. Enhancement of the salt intrusion is comparable between the remote and local winds. Waves decrease the salt intrusion by increasing the water mixing. Sensitivity analysis shows that the axial down-estuary wind, is most efficient in driving increases in salt intrusion via wind straining effect.

GEM: a dynamic tracking model for mesoscale eddies in the ocean - Qiu-Yang Li; Liang Sun; Sheng-Fu Lin (Ocean Science, 2016)
The Genealogical Evolution Model (GEM) presented here is an efficient logical model used to track dynamic evolution of mesoscale eddies in the ocean. It can distinguish between different dynamic processes (e.g., merging and splitting) within a dynamic evolution pattern, which is difficult to accomplish using other tracking methods. To this end, the GEM first uses a two-dimensional (2-D) similarity vector (i.e., a pair of ratios of overlap area between two eddies to the area of each eddy) rather than a scalar to measure the similarity between eddies, which effectively solves the “missing eddy” problem (temporarily lost eddy in tracking). Second, for tracking when an eddy splits, the GEM uses both “parent” (the original eddy) and “child” (eddy split from parent) and the dynamic processes are described as the birth and death of different generations. Additionally, a new look-ahead approach with selection rules effectively simplifies computation and recording. All of the computational steps are linear and do not include iteration. Given the pixel number of the target region L, the maximum number of eddies M, the number N of look-ahead time steps, and the total number of time steps T, the total computer time is O(LM(N + 1)T). The tracking of each eddy is very smooth because we require that the snapshots of each eddy on adjacent days overlap one another. Although eddy splitting or merging is ubiquitous in the ocean, they have different geographic distributions in the North Pacific Ocean. Both the merging and splitting rates of the eddies are high, especially at the western boundary, in currents and in “eddy deserts”. The GEM is useful not only for satellite-based observational data, but also for numerical simulation outputs. It is potentially useful for studying dynamic processes in other related fields, e.g., the dynamics of cyclones in meteorology.